Experiences of Mira Consumption on Mental Health: The Case Somali Youths Refugee Living in Kisenyi Central Division, Kampala - Mohamud Said Barkhad (Uganda Christian University, 2025)
This research focuses on the experience of Mira consumption on mental health of Somali youths residing in Kisenyi central Kampala. Mira is progressively being used by youth in the community, particularly peer groups and ceremonies mainly outside parental control. This research was carried out to investigate the social-economic and psychological factors of Mira use and suggest intervention towards enhancing mental well-being among the consumed. The aim in this research division is to comprehend the ways in which Mira users experience mental well-being in the Somali youth in Kisenyi; by examining how cultural practices and mental outcomes interface, the research aims to produce a detailed information of the Mira consumers and how they impacted disadvantaged community with an eye toward intervention development. The method I have used during my research is qualitative design, data was gathered through using of interviews as well as to interact with individuals particularly snowball sampling techniques to help locate one another. This study employs a qualitative research design in which non numerical data are supported to gain a deeper understanding of experience, attitude, beliefs and identify prospective future participants from the community. This method is especially helpful in accessing hard to reach communities an example being Somali youth who use Mira in Kisenyi. Furthermore obtaining in depth information regarding the attitudes, beliefs and experiences of Somali youth as far as using Mira is concerned. The research concluded that Mira use is not only an adaptive reaction to socio-economic problems but also linked to mental health complication among youths. The research calls for swift action through the implantation of mental health sensitization and education programs for the community. The research suggest that social workers implement ongoing educational outreach while policy makers and the government strengthen more stringent drug control legislation in a bid to reduce youth Mira use.
Undergraduate